Method for regenerating positive electrode active material and positive electrode active material regenerated therefrom
The method regenerates positive electrode active materials from waste lithium secondary batteries by separating the waste battery components using compressed air and solvent treatment, addressing environmental and cost issues, and enhancing battery performance.
Patent Information
- Application Number
- JP2023543195
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-09-14
- Filing Date
- 2022-08-22
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-08-22
AI Technical Summary
Conventional methods for recycling cathode active materials from waste lithium secondary batteries involve the use of acids, leading to environmental pollution, high process costs, and the need for neutralization and wastewater treatment, while also risking toxic gas generation and explosion, and fail to effectively separate the positive electrode from the waste stack battery, affecting battery performance.
A method involving the separation of a waste battery into its components using compressed air to remove the negative electrode, followed by solvent treatment to remove the separation membrane, and subsequent heat treatment and lithium precursor addition to regenerate the positive electrode active material, without the use of acids, thereby ensuring environmental friendliness and process efficiency.
The method allows for the regeneration of positive electrode active materials with improved electrochemical performance, resistance characteristics, and capacity characteristics, while being environmentally friendly and cost-effective, without the risks of toxic gas generation or explosion.
Smart Images

Figure 0007610014000002 
Figure 0007610014000003 
Figure 0007610014000004
Abstract
Description
[Technical Field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0122447, filed on September 14, 2021, and all contents disclosed in the documents of this Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a method for regenerating a cathode active material and a cathode active material regenerated therefrom. More specifically, the present invention relates to a method for regenerating a cathode active material, which significantly improves the rate performance of a battery using the regenerated cathode active material by completely removing ceramic transferred from a separator when recovering a cathode from a waste battery. The method is environmentally friendly because it does not use acid, thereby eliminating the need for neutralization or wastewater treatment, thereby reducing process costs. The method regenerates the cathode active material without decomposition, eliminating the need for discarded metal elements. The current collector is not dissolved in an organic solvent, allowing for recovery. The method does not pose a risk of toxic gas generation or explosion. The method uses easy-to-manage processes, such as heat treatment and compressed air injection, making it suitable for mass production. The present invention also relates to a method for regenerating a cathode active material, which has excellent electrochemical performance, resistance characteristics, and capacity characteristics. [Background technology]
[0003] A lithium secondary battery is generally composed of a positive electrode in which a positive electrode active material layer is coated on a metal foil such as aluminum, a negative electrode in which a negative electrode active material layer is coated on a metal foil such as copper, a separator that prevents the positive and negative electrodes from mixing, and an electrolyte that allows lithium ions to move between the positive and negative electrodes.
[0004] The positive electrode active material layer mainly uses a lithium-based oxide as an active material, and the negative electrode active material layer mainly uses a carbon material as an active material. However, the lithium-based oxide generally contains rare metals such as cobalt, nickel, or manganese. Therefore, much research has been conducted into recovering and reusing rare metals from the positive electrodes of lithium secondary batteries that are discarded after use or from positive electrode scraps generated in the manufacturing process of lithium secondary batteries (hereinafter referred to as "waste positive electrodes").
[0005] Conventional techniques for recovering rare metals from used positive electrodes mostly involve dissolving the used positive electrodes in hydrochloric acid, sulfuric acid, or nitric acid, then extracting cobalt, manganese, nickel, etc. with an organic solvent and using them again as raw materials for synthesizing positive electrode active materials.
[0006] However, the method of extracting rare metals using acid has the disadvantages of causing environmental pollution, requiring a neutralization process and a wastewater treatment process, which significantly increases the process cost, and not allowing the recovery of lithium, the main metal in the positive electrode active material.
[0007] To overcome these drawbacks, direct recycling methods have recently been studied to directly regenerate cathode active materials from waste cathodes without decomposing them. These methods can be broadly divided into four types: calcination, solvent dissolution, aluminum foil dissolution, and crushing and screening.
[0008] However, although the calcination method is simple, it has drawbacks in that foreign matter is generated on the surface of the recycled positive electrode active material, waste gas is generated, and energy consumption is high.
[0009] The solvent dissolution method can produce recycled cathode active materials with relatively clean surfaces, but has the disadvantages of poor stability and the need for an expensive solvent recovery process, since the solvents used to dissolve the binder, such as N-methyl-2-pyrrolidone (NMP), are toxic and explosive.
[0010] The aluminum foil dissolution method has good process stability, low process costs, and easy binder removal, but has drawbacks in that it generates foreign matter that is difficult to remove on the surface of the recycled cathode active material, and hydrogen gas is generated during the aluminum foil removal process, which may pose an explosion risk.
[0011] The crushing and screening method has the advantage of being the simplest process, but has the disadvantages that it is difficult to completely separate the current collector and the positive electrode active material, the particle size distribution of the positive electrode active material changes during the crushing process, and the binder remains, which deteriorates the battery characteristics of the recycled positive electrode active material.
[0012] Furthermore, none of the direct recycling methods for recycled cathode active materials propose a method for cleanly separating cathodes from waste stack batteries. In particular, in pouch-type batteries, ceramic coated on the separator may be transferred to the cathode during rolling in the stacking process. However, if the transferred ceramic is not completely removed from the cathode and remains in the recycled cathode active material, it increases the resistance of the battery and reduces its rate performance.
[0013] Therefore, there is an urgent need to develop a method for easily separating the positive electrode from a waste battery, completely removing the ceramic transferred from the separator during the separation of the positive electrode, thereby improving the rate performance of a battery using a recycled positive electrode active material, and further developing a method for safely and inexpensively recycling the positive electrode active material without using metal elements discarded from the waste positive electrode, in an environmentally friendly manner. Summary of the Invention [Problem to be solved by the invention]
[0014] In order to solve the above-mentioned problems of the prior art, the present invention aims to provide a method for regenerating a cathode active material, which significantly improves the rate performance of a battery using a regenerated cathode active material by completely removing the ceramic transferred from the separator when recovering the cathode from a waste battery; is environmentally friendly because it does not use acid, thereby eliminating the need for neutralization and wastewater treatment, thereby reducing process costs; regenerates the cathode active material without decomposition, so no metal elements are discarded; and the current collector is not dissolved in an organic solvent, so it can be recovered; there is no risk of toxic gas generation or explosion; and the method uses processes that are easy to manage, such as heat treatment and compressed air injection, making it suitable for mass production.
[0015] Another object of the present invention is to provide a positive electrode active material that is excellent in electrochemical performance, resistance characteristics, and capacity characteristics.
[0016] The above and other objects of the present invention can all be achieved by the present invention described below. [Means for solving the problem]
[0017] To achieve the above object, I) the present invention provides a method for regenerating a positive electrode active material, including: (a) crushing waste batteries including a positive electrode, a separator, and a negative electrode; (b) spraying compressed air onto the waste battery pieces to remove the negative electrode; and (c) treating the waste battery pieces from which the negative electrode has been removed with a solvent to remove the separator and obtain positive electrode pieces.
[0018] II) In the step (a) of the method I), the separation membrane may preferably be a ceramic-coated polymer separation membrane.
[0019] III) In the above I) or II), the waste batteries in the step (a) may preferably be stack-type cells.
[0020] IV) In the above I) to III), in the step (a), the waste battery pieces are preferably sized to have an area of 1 cm 2 It may be more than that.
[0021] V) In the above I) to IV), the step (b) may preferably involve injecting compressed air into the waste battery pieces to separate the negative electrode, and then discharging the separated negative electrode using centrifugal force.
[0022] VI) In the above I) to V), in the step (c), the solvent may preferably be a mixed solvent containing acetone and alcohol.
[0023] VII) In the above I) to VI), the alcohol may preferably be ethanol.
[0024] VIII) In the above I) to VII), the mixed solvent may preferably have a weight ratio of acetone to alcohol of 4:6 to 6:4.
[0025] IX) In I) to VIII), the method for regenerating the positive electrode active material may preferably include the step of (d) heat-treating the obtained positive electrode pieces in air at 300 to 650°C to recover the positive electrode active material.
[0026] X) In I) or IX), the method for regenerating a positive electrode active material can preferably include (e) a step of washing the recovered positive electrode active material with water or a basic aqueous lithium compound solution having a concentration of more than 0 wt % and not more than 15 wt %.
[0027] XI) In the above I) to X), the washing in the step (e) may preferably involve mixing and stirring the recovered positive electrode active material with a basic aqueous lithium compound solution.
[0028] XII) In the above I) to XI), the step (e) may preferably be drying the washed positive electrode active material.
[0029] XIII) In the above I) to XII), the method for regenerating a positive electrode active material can preferably include the step of (f) adding a lithium precursor to the washed positive electrode active material and annealing the material in air at 400 to 1000°C.
[0030] XIV) In the above I) to XIII), the lithium precursor may preferably be one or more selected from the group consisting of LiOH, Li2CO3, LiNO3 and Li2O.
[0031] XV) In the above I) to XIV), the method for regenerating a positive electrode active material may preferably further include a step (g) of coating the annealed positive electrode active material with a coating agent containing metal or carbon, followed by heat treatment at 100 to 1200°C.
[0032] XVI) In I) to XV), the positive electrode active material may preferably include at least one selected from the group consisting of lithium cobalt oxides such as LiCoO2 (hereinafter referred to as "LCO"), lithium manganese oxides such as LiMnO2 or LiMn2O4, lithium iron phosphate compounds such as LiFePO4, lithium nickel cobalt aluminum oxide (NCA), lithium nickel cobalt aluminum oxide (NCA), lithium nickel oxides such as LiNiO2, nickel manganese-based lithium composite metal oxides in which part of the nickel (Ni) in the lithium nickel oxide is substituted with manganese (Mn), and NCM-based lithium composite transition metal oxides in which part of the nickel (Ni) in the lithium nickel oxide is substituted with manganese (Mn) and cobalt (Co).
[0033] XVII) In the above I) to XVI), the regenerated positive electrode active material can preferably contain 1 to 10,000 ppm of Al2O3.
[0034] Furthermore, XVIII) the present invention provides a regenerated positive electrode active material produced by the method for regenerating a positive electrode active material in any one of I) to XVII).
[0035] Furthermore, XIX) the present invention provides a regenerative cathode active material comprising at least one selected from the group consisting of lithium cobalt oxides such as LCO; lithium manganese oxides such as LiMnO2 or LiMn2O4; lithium iron phosphate compounds such as LiFePO4; lithium nickel cobalt aluminum oxide (NCA); lithium nickel oxides such as LiNiO2; nickel manganese-based lithium composite metal oxides in which part of the nickel (Ni) in the lithium nickel oxide is substituted with manganese (Mn); and NCM-based lithium composite transition metal oxides in which part of the nickel (Ni) in the lithium nickel oxide is substituted with manganese (Mn) and cobalt (Co), the regenerative cathode active material comprising 1 to 10,000 ppm of Al2O3 and having a surface coated with a coating agent containing metal or carbon.
[0036] XX) In the above XIX), the regenerated positive electrode active material may preferably be a high nickel (High Ni) positive electrode active material having a Ni content of 65 mol % or more relative to the total amount of its metal elements.
[0037] XXI) The present invention also provides a method for recovering positive electrodes, the method including: (a) crushing waste batteries including positive electrodes, separators, and negative electrodes; (b) spraying compressed air onto the waste battery pieces to remove the negative electrodes; and (c) treating the waste battery pieces from which the negative electrodes have been removed with a solvent to remove the separators and obtain positive electrode pieces. [Effects of the Invention]
[0038] According to the present invention, the positive electrode can be easily separated from waste batteries, and the ceramic transferred from the separator is completely removed during this process, thereby significantly improving the rate performance of batteries to which the recycled positive electrode active material is applied. Furthermore, since no acid is used, the method is environmentally friendly, eliminating the need for neutralization and wastewater treatment, thereby reducing process costs. The positive electrode active material is recycled directly without being decomposed, so no metal elements are discarded. The current collector is not dissolved in an organic solvent, so it can be recovered. Furthermore, there is no risk of toxic gas generation or explosion. The method uses easy-to-manage processes, such as heat treatment and compressed air injection, making it suitable for mass production. The present invention also provides a method for regenerating positive electrode active material, which has excellent electrochemical performance, resistance characteristics, and capacity characteristics.
[0039] The following drawings attached to this specification illustrate embodiments of the present invention and, together with the detailed description to be given below, serve to further understand the technical concept of the present invention. Therefore, the present invention should not be interpreted as being limited to the matters described in these drawings. [Brief explanation of the drawings]
[0040] [Figure 1] 1 is a flowchart showing a positive electrode recovery process according to one embodiment of the present invention. [Figure 2] 1 is a flowchart illustrating a process for regenerating a positive electrode active material according to one embodiment of the present invention. [Figure 3] 1 shows photographs of a stack cell (a), a positive electrode (b) before stacking, and the front (c) and rear (d) faces of a positive electrode physically separated from the stack cell in Comparative Example 1. [Figure 4] 1 is a photograph showing a state in which the binder and the conductive material are removed by heat treatment of the positive electrode obtained in Comparative Example 1. [Figure 5]Photographs of a stack cell (a), a stack cell immersed in acetone or a mixed solvent of acetone and alcohol (b), a stack cell swelled and impregnated in acetone or a mixed solvent of acetone and alcohol (c), and the separated positive electrode, negative electrode, and separator (d) in Comparative Example 2. [Figure 6] Photographs taken in Example 1 show (a) the side of a stack & folding cell, (b) the side of a cut stack & folding cell, (c) a stack & folding cell with an air jet sprayed onto the cut side, and (d) the positive electrode, negative electrode, and separator separated after the air jet spray. [Figure 7] 1A is a photograph of a stack cell (a) cut in half and then having a positive electrode, a separation membrane, and a negative electrode separated by an air jet, a positive electrode (b) recovered from the separated stack cell and having a separation membrane transferred thereto, and a negative electrode and a separation membrane (c) recovered from the separated stack cell in Example 2. [Figure 8] Photographs of Example 2 and Comparative Example 3 show the stack cells in the following states: (a, b) treated with acetone or a mixed solvent of acetone and alcohol after air jet injection; and (c, d) treated with acetone or a mixed solvent of acetone and alcohol without air jet injection. [Figure 9] 1 shows photographs of an electrode piece (c) obtained after cutting the stack cell (a, b) into a 3 cm × 3 cm piece in Example 3, and a positive electrode (d) and a negative electrode and a separation membrane (e) separated and recovered by treating the electrode piece with an air jet. [Figure 10] 10 is a photograph showing the state in Example 4 where the stack cell was cut into 1 cm x 1 cm pieces and then treated with an air jet. [Figure 11] 1 is a graph showing the results of cell evaluation of the recycled positive electrode active materials prepared in Examples 5 to 7 and Comparative Example 4 and the positive electrode active material of Reference Example (Reference NCM65), illustrating the rate performance as a function of the number of cycles. DETAILED DESCRIPTION OF THE INVENTION
[0041] The inventors have been researching a direct recycling method for recycling used positive electrodes into positive electrode active material without decomposing the positive electrode active material. They discovered that by cutting used pouch cells or rolled bi-cells made of separators to a predetermined size, and then spraying compressed air onto them to separate and remove the low-density negative electrodes and some of the separators, and then immersing the remaining positive electrodes and separators in acetone or an acetone-containing solution to remove the separator and obtain a positive electrode, both the positive and negative electrodes can be reused. In particular, they found that the battery characteristics of the positive electrode active material recycled from the obtained positive electrodes were significantly improved. Based on this finding, they conducted further research and completed the present invention.
[0042] The presently described method for recovering a positive electrode, the method for regenerating a positive electrode active material, and the positive electrode active material regenerated therefrom will be described in detail below.
[0043] However, the terms and words used in this specification and claims should not be construed as being limited to their ordinary or dictionary meanings, but should be construed as meanings and concepts consistent with the technical idea of the present invention, based on the principle that the inventor can appropriately define the concepts of terms in order to best describe his or her invention. Therefore, it should be understood that the embodiments described in this specification and the configurations shown in the drawings are merely one embodiment of the present invention and do not represent the entire technical idea of the present invention, and therefore various equivalents and modifications that can be substituted for them may exist, and they may be arranged, substituted, combined, separated, or designed in various other configurations.
[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0045] Method for recovering positive electrodes and method for regenerating positive electrode active material The method for recovering positive electrodes and the method for regenerating positive electrode active material of the present invention include the steps of (a) crushing used batteries containing positive electrodes, separators, and negative electrodes; (b) spraying compressed air onto the used battery pieces to remove the negative electrodes; and (c) treating the used battery pieces from which the negative electrodes have been removed with a solvent to remove the separator and obtain positive electrode pieces. In this case, both the positive electrodes and negative electrodes are reusable, and positive electrodes can be easily recovered from used batteries. In particular, removing the ceramic transferred from the separator significantly improves the rate performance of batteries to which the recycled positive electrode active material is applied. Furthermore, since no acid is used, the method is environmentally friendly, eliminating the need for neutralization and wastewater treatment, thereby reducing process costs. Since the positive electrode active material is regenerated directly without decomposition, no metal elements are discarded. Furthermore, since the current collector is not dissolved in an organic solvent, it is recoverable. Furthermore, there is no risk of toxic gas generation or explosion. The method uses easy-to-manage processes, such as heat treatment and compressed air spraying, making it suitable for mass production.
[0046] (a) Crushing waste batteries The step (a) of crushing waste batteries according to the present invention may preferably be a step of crushing waste batteries including positive electrodes, separators, and negative electrodes.
[0047] In this description, waste batteries refer to used or unusable lithium secondary battery electrodes, bi-cells, stack cells, modules, etc.
[0048] The separator may be preferably a ceramic-coated polymer separator, which prevents shrinkage due to heat and improves thermal stability and electrochemical properties.
[0049] For example, the ceramic may include one or more metal oxides or metal compounds containing one or more metal components, and specific examples thereof include one or more selected from the group consisting of CaCO3, Al2O3, SiO2, BaTiO3, TiO2, talc (Talc), ZrO, WO3, and Al(OH)3. When such metal oxides or metal compounds are added to the separator, they can prevent shrinkage due to heat, thereby improving thermal stability and electrochemical properties.
[0050] The ceramic may have an average diameter of, for example, 0.1 to 2 μm, and within this range, shrinkage due to heat is prevented, thereby improving thermal stability and electrochemical properties.
[0051] In this description, the average diameter can be measured by a measurement method commonly used in the technical field to which the present invention pertains, for example, by using a laser diffraction method. Specifically, particles of a positive electrode active material can be dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size analyzer such as a Microtrac MT 3000. Ultrasonic waves of about 28 kHz and an output of 60 W can be irradiated to calculate the average particle size (D50) based on 50% of the particle size distribution measured by the analyzer.
[0052] The coating may be, by way of example, a gravure printing coating, a dip-coating, or a spray coating.
[0053] The method for coating the ceramic on the polymeric separation membrane may be, for example, gravure printing, dip-coating, or spray coating of a slurry containing ceramic, a binder, and water on the polymeric separation membrane.
[0054] The binder is not particularly limited as long as it is a binder commonly used in the technical field to which the present invention pertains, and may be, for example, at least one selected from the group consisting of (meth)acrylate polymers, (meth)acrylate-styrene copolymers, (meth)acrylate-acrylonitrile copolymers, silicon-acrylate copolymers, epoxy compound-acrylate copolymers, polybutadiene, polyisoprene, butadiene-styrene random copolymers, isoprene-styrene copolymers, acrylonitrile-butadiene copolymers, acrylonitrile-butadiene-styrene copolymers, butadiene-styrene block copolymers, and styrene-butadiene-styrene block copolymers.
[0055] In this description, (meth)acrylate is meant to include both acrylate and methacrylate.
[0056] The waste batteries in step (a) preferably include stack-type cells, and more preferably may be pouch cells, which has the advantage that the objects and effects of the present invention can be more effectively achieved.
[0057] In the case of the pouch cell, electrodes must be stacked, so the cathode / separator / anode of the electrodes are laminated at high temperature, and the ceramic coated on the separator may be transferred to the cathode.
[0058] In the step (a), the size of the waste battery pieces is not particularly limited because the separation efficiency may vary depending on the experimental conditions and equipment. For example, when the experimental conditions and equipment of the following embodiment are used, the area (width x length) of the waste battery pieces is 1 cm 2 More than 2cm 2 or more than 3cm 2 or more, or 1m 2 Below, 50cm 2 Less than or equal to 10cm 2 The thickness may be less than this range, and within this range, there is an advantage that the process is easy.
[0059] (b) Removing the negative electrode by spraying compressed air The step (b) of spraying compressed air to remove the negative electrode according to the present invention may preferably be a step of spraying compressed air onto the waste battery pieces to remove the negative electrode. In this case, both the positive electrode and the negative electrode are reusable, the positive electrode can be easily recovered from the waste battery, and in particular, there is an effect of removing a considerable amount of ceramic and the like transferred from the separator.
[0060] The compressed air may be injected using any ordinary compressed air injection device without any particular limitation, and examples thereof include a compressed air injector, an air spray, and an air gun.
[0061] The injection pressure of the compressed air may be, for example, 0.5 bar or more, or 1 bar or more, and is preferably 2 bar or more, which has the advantage that separation of the negative electrode occurs more easily.
[0062] The injection pressure may be adjusted depending on the number, size, or state of the stacks, and its upper limit is not particularly limited. However, when considering the cost of the device, it may be limited to a maximum of 100 bar per kg of waste batteries such as waste stack cells, for example.
[0063] The step (b) may preferably involve injecting compressed air into the waste electrode pieces to separate the negative electrode, and then discharging the separated negative electrode using centrifugal force and / or a difference in specific gravity. Since the negative electrode has a specific gravity that is approximately 1.2 to 3 times lower than that of the positive electrode, the use of centrifugal force or a difference in specific gravity makes it possible to separate the negative electrode or the separation membrane.
[0064] (c) Removing the separator and obtaining the positive electrode pieces The step (c) of removing the separator and obtaining the positive electrode pieces according to the present invention may preferably be a step (c) of treating the waste battery pieces from which the negative electrode has been removed with a solvent to remove the separator and obtain the positive electrode pieces. In this case, removing the ceramic transferred from the separator has the effect of significantly improving the rate performance of the battery to which the recycled positive electrode active material is applied.
[0065] In the step (c), the solvent may be a mixed solvent preferably containing acetone and alcohol, which has the advantage that the positive electrode components are not eluted and only the transferred ceramic is removed.
[0066] The alcohol may preferably be ethanol, which has the advantage that the positive electrode components are not eluted and only the transferred ceramic is removed.
[0067] The mixed solvent may preferably have a weight ratio of acetone to alcohol of 2:8 to 8:2, more preferably 6:4 to 4:6. Within this range, there is an advantage that the positive electrode components are not eluted and only the transferred ceramic is removed.
[0068] The mixed solvent preferably contains water in an amount of 5 wt % or less, more preferably less than 5 wt %, even more preferably 3 wt % or less, and even more preferably 2 wt % or less. Within this range, gelation of the binder is suppressed, thereby preventing gel adhesion that makes ceramic separation difficult.
[0069] (d) Recovering the positive electrode active material from the waste positive electrodes The step (d) of recovering a positive electrode active material from a used positive electrode according to the present invention may preferably be a step of recovering the positive electrode active material by heat-treating a used positive electrode including a current collector and a positive electrode active material layer coated thereon in air at 300 to 650°C. In this case, the process is simple and has the effect of completely removing the binder, conductive material, and current collector.
[0070] The positive electrode active material layer preferably can contain a positive electrode active material, a binder, and a conductive material.
[0071] The positive electrode active material is preferably at least one selected from the group consisting of lithium cobalt oxide such as LCO; lithium manganese oxide such as LiMnO2 or LiMn2O4; lithium iron phosphate compound such as LiFePO4; lithium nickel cobalt aluminum oxide (NCA; lithium nickel cobalt aluminum oxide); lithium nickel oxide such as LiNiO2; nickel manganese-based lithium composite metal oxide in which part of nickel (Ni) in the lithium nickel oxide is substituted with manganese (Mn); and NCM-based lithium composite transition metal oxide in which part of nickel (Ni) in the lithium nickel oxide is substituted with manganese (Mn) and cobalt (Co). More preferably, it is a nickel manganese-based lithium composite metal oxide, an NCM-based lithium composite transition metal oxide, or a mixture thereof. In this case, there is an effect of excellent reversible capacity and thermal stability.
[0072] As still another specific example, the positive electrode active material has the following Chemical Formula 1 [Chemical Formula 1] Li a Ni x Mn y Co z M w O 2+δ (In Chemical Formula 1, M contains at least one selected from the group consisting of B, W, Al, Ti, and Mg, and 1 < a ≤ 1.1, 0 < x < 0.95, 0 < y < 0.8, 0 < z < 1.0, 0 ≤ w ≤ 0.1, -0.02 ≤ δ ≤ 0.02, and x + y + z + w = 1.) It may be a compound represented by.
[0073] The positive electrode active material may preferably be a high nickel (High Ni) positive electrode active material having a Ni content of 65 mol% or more based on the total amount of its metal elements.
[0074] The conductive material may be, for example, a carbon-based conductive material, and preferably, carbon black, graphite, or a mixture thereof.
[0075] The binder may be, for example, a polymer binder, preferably polyvinylidene fluoride (PVdF), acrylonitrile-butadiene rubber (NBR), or a mixture thereof, and more preferably polyvinylidene fluoride.
[0076] The heat treatment temperature may be preferably 400 to 600°C, more preferably 500 to 600°C, and even more preferably 530 to 570°C. Within this range, the current collector is not dissolved and only the binder and the like are removed, which has the advantage that the positive electrode active material can be easily separated from the current collector.
[0077] The heat treatment time may be preferably 10 minutes to 5 hours, more preferably 30 minutes to 5 hours, even more preferably 30 minutes to 2 hours, and even more preferably 30 minutes to 1 hour. Within this range, the current collector is not dissolved and only the binder and the like are removed, which has the advantage that the positive electrode active material can be easily separated from the current collector.
[0078] In this description, the heat treatment time refers to the time required for treatment at the heat treatment temperature, and does not include the time required to reach the heat treatment temperature.
[0079] (e) washing with water or a basic aqueous solution of a lithium compound; The step (e) of washing with water or a basic aqueous lithium compound solution according to the present invention may preferably be a step of washing the recovered positive electrode active material with a basic aqueous lithium compound solution having a concentration of more than 0 wt % and not more than 15 wt %. In this case, as a step of modifying the surface of the positive electrode active material, it has the effect of removing foreign matter such as LiF or metal fluorides generated on the surface of the positive electrode active material during the previous heat treatment process.
[0080] The recovered positive electrode active material may be washed by adding 0.1 to 100 g per 100 ml of a basic lithium compound aqueous solution, mixing or immersing, more preferably by adding 0.1 to 50 g of the positive electrode active material per 100 ml of a basic lithium compound aqueous solution, mixing or immersing, and washing. Within this range, foreign matter such as LiF or metal fluoride generated on the surface of the positive electrode active material during the previous heat treatment process can be effectively removed as a step for modifying the surface of the positive electrode active material.
[0081] The basic lithium compound aqueous solution in step (e) preferably contains more than 0 wt. % to 10 wt. % of the basic lithium compound, more preferably more than 0 wt. % to 5 wt. This range serves to remove foreign matter, such as LiF or metal fluorides, that may have formed on the surface of the positive electrode active material during the heat treatment process, which serves as a surface modification process for the positive electrode active material. The LiF can be left on the surface of the positive electrode active material without being removed. While this may result in a partial decrease in battery capacity, the presence of LiF on the surface of the positive electrode active material can inhibit side reactions between the positive electrode active material and the electrolyte, thereby improving battery life. Therefore, if desired, the LiF can be left as is, or, if desired, can be removed by washing with the basic lithium compound aqueous solution, as described above.
[0082] The washing may preferably be performed by stirring the recovered positive electrode active material in a basic aqueous lithium compound solution. In this case, as a step of modifying the surface of the positive electrode active material, it is effective in removing foreign matter such as LiF or metal fluorides generated on the surface of the positive electrode active material during the previous heat treatment process.
[0083] The stirring may be carried out for, for example, within one week, preferably within one day, more preferably for one hour or less, 40 minutes or less, 30 minutes or less, or 20 minutes or less, or for, for example, 5 minutes or more, preferably 10 minutes or more, 20 minutes or more, or 30 minutes or more. Within this range, all foreign matter such as LiF or metal fluoride generated on the surface of the positive electrode active material is removed, and there is no excessive elution of lithium, which is advantageous in that the capacity characteristics of the battery are excellent.
[0084] In step (e), preferably, after the mixing, immersion, or stirring is completed, the positive electrode active material may be recovered and dried. In this case, the process of adding the lithium precursor may be optimized.
[0085] The drying can be carried out preferably at 70 to 200°C, more preferably at 20 to 130°C until there is no further change in weight, for example, for 1 to 24 hours. Within this range, the moisture contained in the settled active material can be effectively removed.
[0086] (f) adding a lithium precursor and then annealing The step (f) of adding a lithium precursor and then annealing according to the present invention may preferably be a step of adding a lithium precursor to the washed cathode active material and annealing it in air at 400 to 1000°C. In this case, the battery characteristics of the regenerated cathode active material can be improved by improving the crystallinity, such as by increasing the crystallinity or restoring the crystal structure.
[0087] The lithium precursor may preferably be one or more selected from the group consisting of LiOH, Li2CO3, LiNO3 and Li2O.
[0088] The lithium precursor is preferably added in an amount corresponding to the difference between the molar ratio of lithium in the cathode active material in step (d), i.e., the newly generated cathode active material, and the molar ratio of lithium in at least the reduced precipitate, based on the amount of lithium. More preferably, the lithium precursor is added in an amount that results in a molar ratio of lithium of 0.0001 to 0.2 relative to the molar ratio of lithium in the cathode active material in step (d). Within this range, the deficient lithium in the regenerated cathode active material is replenished, and crystallinity is improved, such as by increasing crystallinity or restoring the crystal structure, thereby improving the battery characteristics of the regenerated cathode active material.
[0089] In this description, if there is a difference in the molar ratio of elements between the positive electrode active material in step (d) and the new positive electrode active material, the molar ratio of elements in the new positive electrode active material is preferably used as the basis.
[0090] The lithium precursor may be added in an amount that provides 1 to 40 mol% of lithium based on a total of 100 mol% of lithium in the cathode active material in step (d), i.e., the newly generated cathode active material, more preferably in an amount that provides 1 to 15 mol%, and even more preferably in an amount that provides 7 to 12 mol% of lithium. Within this range, no residual precursor that may increase resistance remains in the regenerated cathode active material, which is very useful for improving battery characteristics.
[0091] The annealing temperature can be adjusted within a limited range depending on the melting point of the lithium precursor. For example, since the melting point of LiCO is 723°C, annealing can be preferably performed at 700 to 900°C, more preferably 710 to 780°C. Since the melting point of LiOH is 462°C, annealing can be preferably performed at 400 to 600°C, more preferably 450 to 480°C. Within this range, the crystal structure is restored, resulting in excellent battery output performance.
[0092] The annealing temperature may preferably be a temperature exceeding the melting point of the lithium precursor, but if it exceeds 1000°C, thermal decomposition of the positive electrode active material may occur, resulting in a decrease in battery performance.
[0093] (f') Removal step of residual lithium precursor The step (f') of removing the residual lithium precursor according to the present invention is an optional step and can be adopted in the present invention when necessary, such as when excessive residual lithium remains. Preferably, the step may be a step of washing the annealed positive electrode active material with a washing solution. In this case, by removing the residual lithium precursor that did not participate in the reaction during the annealing process, it is possible to fundamentally prevent solidification, swelling, gas generation, etc. caused by the residual lithium precursor in the subsequent electrode manufacturing process.
[0094] For example, if the residual lithium precursor that did not participate in the reaction during the annealing process is LiOH, it increases the pH of the slurry that forms the positive electrode active material layer, accelerating the solidification phenomenon and making it difficult to manufacture a uniform positive electrode plate. If the residual lithium precursor is Li2CO3, it increases the swelling phenomenon of the cell, reducing the cycle life and causing the battery to swell.
[0095] The step (f') of removing the residual lithium precursor may preferably include washing the annealed cathode active material with a washing solution and heat-treating the washed cathode active material. In this case, the residual lithium precursor is removed, and the surface area of the cathode active material is increased, the resistance is reduced, and the discharge capacity is increased.
[0096] The step (f') of removing the residual lithium precursor may preferably include washing the annealed cathode active material with a washing solution, drying the washed cathode active material, and heat-treating the dried cathode active material. In this case, the residual lithium precursor is removed, and the surface area of the cathode active material is increased, the resistance is reduced, and the discharge capacity is increased.
[0097] The cleaning solution is not particularly limited as long as it is a cleaning solution generally used in the technical field to which the present invention belongs to for removing residual lithium precursors such as LiOH, Li2CO3, etc., and may be, for example, distilled water or ion-exchanged water.
[0098] For example, the washing may be performed by adding 5 g to 2 kg of the annealed positive electrode active material per 1 L of washing solution, stirring, and then filtering. Preferably, the washing may be performed by adding 10 g to 1 kg of the annealed positive electrode active material per 1 L of washing solution, stirring, and then filtering. More preferably, the washing may be performed by adding 20 g to 100 g of the annealed positive electrode active material per 1 L of washing solution, stirring, and then filtering. Within these ranges, residual lithium precursors are removed, the surface area of the positive electrode active material is increased, the resistance is reduced, and the discharge capacity is increased.
[0099] As yet another example, the washing may be performed in a weight ratio of annealed positive electrode active material to washing solution within a range of 1:0.5 to 1:5, and as a preferred example, within a range of 1:0.5 to 1:2, which has the advantage of excellent washing efficiency.
[0100] The washing time may be, for example, 0.1 to 72 hours, and preferably 24 hours or less. In this case, the residual lithium precursor is removed, the surface area of the positive electrode active material is increased, the resistance is reduced, and the discharge capacity is increased.
[0101] In this description, the washing time is defined as the time immediately after mixing and before filtering, and may be, by way of example, the mixing and / or stirring time.
[0102] The drying may be, for example, vacuum drying at 50 to 200°C, preferably at 70 to 130°C. Within this range, residual lithium precursors are removed, the surface area of the positive electrode active material is increased, the resistance is reduced, and the discharge capacity is increased.
[0103] For example, the heat treatment may be performed at 200 to 900°C for 2 to 24 hours in an air or oxygen (O2) atmosphere, and preferably at 700 to 800°C for 2 to 15 hours. Within this range, residual lithium precursors are removed, the surface area of the positive electrode active material is increased, the resistance is reduced, and the discharge capacity is increased.
[0104] (g) A step of coating with a coating agent and then heat treating the coating. The step (g) of coating with a coating agent and then heat-treating according to the present invention is an optional step, and preferably, the annealed cathode active material of step (f) or (f') may be coated with a coating agent containing metal or carbon, followed by heat-treating at 200 to 1000°C. In this case, side reactions caused by the electrolyte are prevented, and structural stability and electrochemical performance are improved while maintaining the properties of the cathode active material itself.
[0105] The metal-containing coating agent is preferably a coating agent containing one or more selected from the group consisting of B, W, Al, Ti, Mg, Ni, Co, Mn, Si, Zr, Ge, Sn, Cr, Fe, V, and Y, and more preferably a coating agent containing one or more selected from the group consisting of B, W, Al, Ti, and Mg. In this case, there is an effect that metals other than lithium or the surface coating layer lost during the current collector separation process and the positive electrode active material surface modification process are replenished or restored.
[0106] The heat treatment temperature may be preferably 200 to 900°C, more preferably 200 to 700°C, and even more preferably 200 to 500°C. Within this range, performance degradation due to thermal decomposition of the positive electrode active material does not occur, and side reactions caused by the electrolyte are prevented, thereby improving structural stability and electrochemical performance while maintaining the properties of the positive electrode active material itself.
[0107] As a specific example, when the coating agent contains B, BW, B-Ti, or BW-Ti, the heat treatment temperature is preferably 200 to 500°C.
[0108] The coating agent may be preferably 0.01 to 10 parts by weight, more preferably 0.1 to 1 part by weight, based on 100 parts by weight of the total positive electrode active material. Within this range, the properties of the positive electrode active material itself are maintained as they are, while the structural stability and electrochemical performance are improved.
[0109] The heat treatment time is preferably 1 to 16 hours, more preferably 3 to 7 hours. Within this range, the properties of the positive electrode active material itself are maintained, while the structural stability and electrochemical performance are improved.
[0110] The coating method is not particularly limited as long as it is a coating method commonly used in the technical field to which the present invention pertains, and examples thereof include a liquid phase method in which a liquid coating agent is prepared and mixed with a positive electrode active material, a mechanochemical method using high mechanical energy such as ball milling, a fluidized bed coating method, a spray drying method, a precipitation method in which a coating agent in an aqueous solution is precipitated on the surface of an active material, a method utilizing a reaction between a gaseous coating agent and a positive electrode active material, and a sputtering method.
[0111] The coating agent may be, for example, spherical, plate-like, angular, or needle-like, and such a shape can be adjusted, for example, by changing process conditions during the manufacturing process, and is not particularly limited as long as it follows the definition commonly accepted in the technical field to which the present invention belongs.
[0112] The coating agent preferably has an average diameter of 1 to 1000 nm and a specific surface area of 10 to 100 m 2 / g, and more preferably, the average diameter is 10 to 100 nm and the specific surface area is 20 to 100 m 2 / g, and within this range, the particles are uniformly attached to the surface of the positive electrode active material, imparting structural stability to the positive electrode active material, thereby improving the problems of deterioration in life characteristics and electrochemical performance due to lattice deformation and collapse of the crystal structure of the positive electrode active material.
[0113] In this description, the specific surface area can be measured by a measurement method commonly used in the technical field to which the present invention pertains, for example, by the BET (Brunauer-Emmett-Teller) method, and specifically, can be calculated from the amount of nitrogen gas adsorbed at liquid nitrogen temperature (77 K) using a BELSORP-mino II from BEL Japan.
[0114] FIG. 1 below is a flowchart showing a positive electrode recovery process according to one embodiment of the present invention.
[0115] 1, first, a used stack cell that has been used as a lithium secondary battery is prepared (step S10). Here, the used stack cell includes high nickel (high Ni) (nickel ratio of 60 mol% or more) as a positive electrode active material and a ceramic-coated polymer separator as a separator.
[0116] Next, the prepared waste stack cells are crushed to an appropriate size (step S20). Here, crushing involves cutting or shredding the waste stack cells using compressed air into sizes that are easy to separate and handle. As a specific example, the crushed waste stack cell pieces may be approximately 3 cm x 3 cm in size. For example, the crushing may be performed using various dry crushing equipment such as a hand mill, pin mill, disc mill, cutting mill, or hammer mill, or a high-speed cutting machine may be used to increase productivity.
[0117] Next, compressed air is sprayed onto the waste stack cell pieces to remove the negative electrodes and some of the separation membranes (step S30). At this time, the negative electrodes and separation membranes, which have low specific gravity, are discharged from the separation container, and only the positive electrodes, which have high specific gravity, remain in the separation container. Here, the specific gravity of the positive electrodes is 2 to 3 times higher than that of the negative electrodes.
[0118] Next, the waste stack cell pieces from which the negative electrode and a portion of the separator are removed are placed in a mixed solvent of acetone and ethanol, and are immersed and stirred for 10 to 30 minutes to separate the separator into a supernatant liquid, which is then removed together with the supernatant liquid to obtain clean waste positive electrode pieces.
[0119] In the case of stack cells, the separator bonding process involves laminating the cathode at high temperatures, which can result in the ceramic in the separator being transferred to the cathode. If the cathode is directly shredded and the current collector is separated while the separator is still attached, the ceramic content will increase. To overcome this, the stack cell is immersed in acetone or a solution containing acetone (hereinafter referred to as the "acetone solution") according to the present invention, which removes the ceramic transferred to the cathode, resulting in a clean cathode.
[0120] When a cathode active material is regenerated, the charge / discharge capacity expression rate of the regenerated cathode active material is affected by whether or not a ceramic removal process is performed, but by removing the ceramic through an acetone solution immersion process according to the present invention, the capacity expression rate of the regenerated cathode active material is significantly increased. Here, the type of ceramic used to coat the separator is not limited.
[0121] FIG. 2 below is a flowchart of a process for regenerating a positive electrode active material according to one embodiment of the present invention.
[0122] 2, first, scrap cathode fragments obtained in the previous step are prepared (step S50). For example, a new cathode can be produced by mixing NCM-based lithium transition metal composite oxide, carbon black, and polyvinylidene fluoride with N-methyl pyrrolidone (NMP) to form a slurry, coating the slurry on aluminum foil, and drying it in a vacuum oven at approximately 120°C.
[0123] The waste cathode pieces have a cathode active material layer on an aluminum foil, and the cathode active material layer has a structure in which the cathode active material and the conductive material are bound by a binder after the solvent evaporates. Therefore, the cathode active material can be separated from the aluminum foil by removing the binder.
[0124] For example, whether or not to crush the waste cathode pieces, and the size of the pieces, can be determined taking into consideration the handling of the waste cathode pieces and the characteristics required for the equipment used in subsequent processes. For example, when using equipment capable of continuous processing, the waste cathode pieces must have good fluidity, so the waste cathode pieces can be crushed into smaller pieces.
[0125] Next, the discarded positive electrode pieces are heat-treated in air (step S60), where the heat treatment is carried out to thermally decompose the binder in the active material layer.
[0126] Through the heat treatment in air, the binder and conductive material in the active material layer are thermally decomposed into CO2 and HO and removed. Because the binder is removed, the active material is separated from the current collector, and the separated active material can be easily sorted in powder form. Therefore, by performing only step S60, the active material layer can be separated from the current collector, and the active material in the active material layer can be recovered in powder form.
[0127] It is important that the heat treatment be carried out in air. However, if the heat treatment is carried out in a reducing gas or inert gas atmosphere, the binder and conductive material will carbonize without being thermally decomposed. Carbonization leaves carbon components on the surface of the active material, reducing the performance of the recycled active material. However, if the heat treatment is carried out in air, the carbon components in the binder and conductive material react with oxygen and disappear as gases such as CO and CO2, removing both the binder and conductive material.
[0128] The heat treatment is preferably carried out at 300 to 650°C, specifically at 550°C. If the temperature is lower than 300°C, it is difficult to remove the binder, making it impossible to separate the current collector. If the temperature exceeds 650°C, the current collector melts, making it impossible to separate the current collector.
[0129] The heat treatment is preferably carried out at a temperature increase rate of 1 to 20°C / min, more preferably 3 to 10°C / min, specifically 5°C / min. Within this range, the heat treatment can be carried out without placing strain on the heat treatment equipment, and there are advantages in that no thermal shock or the like is caused to the cathode scrap.
[0130] The heat treatment can be carried out for a period of time sufficient to thermally decompose the binder, preferably for 30 minutes or more, more preferably for 30 minutes to 5 hours, and specifically for about 30 minutes. Within this range, the binder is sufficiently thermally decomposed and the thermal decomposition efficiency is excellent.
[0131] The heat treatment may be carried out using various types of furnaces, for example, a box-type furnace, or, in consideration of productivity, a rotary kiln capable of continuous treatment.
[0132] After the heat treatment, the material can be cooled slowly or rapidly in the air.
[0133] Next, as a surface modification step, the recovered active material is washed (step S70).
[0134] The cleaning removes reactants that may have been generated on the surface of the active material during the heat treatment step (S60) to prevent foreign matter from remaining on the surface of the recycled material.
[0135] It is important to use a basic aqueous solution of a lithium compound during the cleaning process. If an aqueous solution of sulfuric acid or hydrochloric acid is used, it will be possible to clean foreign matter such as fluorine (F) compounds from the surface of the positive electrode active material, but it will also dissolve transition metals such as Co and Mg present in the positive electrode active material, thereby reducing the performance of the regenerated positive electrode active material.
[0136] However, the basic lithium compound aqueous solution is highly preferred because it is safe and inexpensive, and can remove binders and the like that may remain in trace amounts even after the thermal decomposition in step S60 without causing loss of other elements, and can also replenish the amount of lithium that may be eluted during the cleaning process without eluting transition metals present in the positive electrode active material.
[0137] The basic lithium compound aqueous solution contains, for example, more than 0% and not more than 15% of the basic lithium compound. A lithium compound aqueous solution with a higher concentration than this may leave an excessive amount of lithium compound on the surface of the active material after washing, which may adversely affect the subsequent annealing step.
[0138] The washing can be carried out, for example, by adding 1 to 5 g of the recovered positive electrode active material per 100 mL of a basic lithium compound aqueous solution and immersing or stirring the solution. The stirring method is not particularly limited, and may be mechanical stirring or ultrasonic stirring.
[0139] The lithium compound is preferably LiOH.
[0140] In this description, % means % by weight unless otherwise specified.
[0141] The washing is carried out for 10 to 20 minutes as a specific example, and within this range, it is effective to prevent a decrease in battery capacity due to excessive elution of lithium.
[0142] In this description, the reason for washing the recovered cathode active material with a basic lithium compound aqueous solution is to perform surface modification by removing LiF and metal fluorides that may be present on the surface of the recovered cathode active material. During the heat treatment in step S60, the binder and conductive material in the active material layer are converted into CO2 and HO, which are vaporized and removed. During this process, CO2 and HO may react with lithium on the surface of the active material to form Li2CO3 and LiOH. Furthermore, F present in binders such as PVdF may react with lithium and other metal elements that make up the cathode active material to form LiF or metal fluorides. If such LiF or metal fluorides remain on the surface of the cathode active material, battery performance may deteriorate during reuse.
[0143] After the washing, the positive electrode active material slurry is filtered or the supernatant is decanted to obtain the solid positive electrode active material.
[0144] The obtained positive electrode active material is dried in air using, for example, a convection type oven.
[0145] Next, a lithium precursor is added to the dried positive electrode active material, and annealing is performed (step S80).
[0146] Because lithium loss occurs within the positive electrode active material during steps S50, S60, and S70, step S80 replenishes this lost lithium. Furthermore, because a deformed structure (e.g., Co3O4 in the case of an LCO active material) may develop on the surface of the positive electrode active material during these steps, step S80 involves annealing to restore the crystalline structure of the positive electrode active material, thereby improving the characteristics of the regenerated positive electrode active material or restoring it to the level of a virgin positive electrode active material. Here, "virgin" is the opposite concept of "regenerated," meaning that the material is newly produced, and is the same term as "raw material" used in the embodiments.
[0147] As the lithium precursor, LiOH is specifically used.
[0148] The lithium precursor is preferably added in an amount corresponding to the molar ratio of lithium lost relative to the molar ratio of lithium to other metals in the new cathode active material used in the cathode active material layer. Adding an amount of lithium precursor that is excessively greater than the amount of lost lithium leaves unreacted lithium precursor in the regenerated cathode active material, which increases resistance, so it is necessary to add an appropriate amount of lithium precursor. For example, if the molar ratio of lithium to other metals in the new cathode active material is 1, the lithium precursor can be added in an amount that results in a lithium molar ratio of 0.001 to 0.4, preferably 0.01 to 0.2.
[0149] Specifically, when a lithium precursor is added in a molar ratio of 0.09 to 0.1 (based on lithium metal), which is the ratio of the lithium content lost to the newly produced positive electrode active material based on the results of ICP analysis, the capacity improvement effect is equivalent to that of the newly produced positive electrode active material. Here, the results of ICP analysis have an error value of about ±0.02.
[0150] The annealing is carried out in air at a temperature of, for example, 400 to 1000°C, preferably 600 to 900°C, and this temperature must be varied within a limited range depending on the type of lithium precursor.
[0151] The annealing temperature is preferably a temperature exceeding the melting point of the lithium precursor. However, temperatures exceeding 1000°C may cause thermal decomposition of the positive electrode active material, resulting in a decrease in performance, so the temperature should not exceed 1000°C. Therefore, when Li2CO3 is used as the lithium precursor, the annealing temperature is preferably 700 to 900°C, more preferably 710 to 780°C, and most preferably 750 to 780°C. When LiOH is used as the lithium precursor, the annealing temperature is preferably 400 to 600°C, more preferably 450 to 480°C, and most preferably 470 to 480°C.
[0152] The annealing time is, for example, 1 hour or more, preferably 15 hours or less, and more preferably 4 to 6 hours. A longer annealing time may allow sufficient recovery of the crystal structure, but even if annealing is performed for a long period of time, the performance is not significantly affected. The annealing equipment may be the same as or similar to that used in the heat treatment step S60.
[0153] The annealing step is safe and inexpensive, and restores the crystalline structure, i.e., improves the crystallinity, thereby restoring the battery characteristics of the regenerated positive electrode active material.
[0154] The recycled cathode active material obtained through the above-described cathode active material recycling step has a particle size distribution similar to that of the virgin cathode active material, and does not contain any carbon components on the surface that are generated by carbonization of the binder or conductive material. Therefore, it can be used to manufacture a cathode 100% as is or by mixing with virgin materials without any additional processing.
[0155] Next, as an optional step, the annealed positive electrode active material is washed with a washing solution to remove any lithium precursor remaining on the surface of the positive electrode active material (step S90).
[0156] Next, as an optional step, the annealed positive electrode active material may be further subjected to a surface coating (S100).
[0157] For example, the surface coating is performed by coating the surface with a coating agent containing metal or carbon in a solid or liquid phase manner, followed by heat treatment at 100 to 1200°C. If the heat treatment temperature is less than 100°C, a surface protective layer made of a different metal is not formed through the surface coating, and if the heat treatment temperature is more than 1200°C, the battery performance is reduced due to thermal decomposition of the positive electrode active material.
[0158] Specifically, when metal oxides such as B, W, and B-W are coated on the positive electrode active material and then heat-treated, a lithium boron oxide layer can be formed on the surface of the active material, which acts as a surface protection layer.
[0159] The solid or liquid phase method of the surface coating may be carried out by, for example, mixing, milling, spray drying, or grinding.
[0160] For reference, if the molar ratio of lithium to other metals in the positive electrode active material is set to 1:1 in the previous annealing step S80, and the lithium in the positive electrode active material reacts with the coating agent, causing the molar ratio of lithium to other metals in the positive electrode active material to decrease below 1:1, the battery's capacity cannot be fully realized. Therefore, the missing lithium is not only added in the previous step S80 to achieve a 1:1 molar ratio of lithium to other metals in the positive electrode active material, but also added in excess so that the lithium is present in an amount of 0.0001 to 0.1 molar ratio greater than the other metals in the positive electrode active material. This ensures that the molar ratio of lithium to other metals in the positive electrode active material is 1:1 during the surface coating step S100, and also forms a surface protective layer.
[0161] Specifically, the lithium added in excess of about 0.0001 to 0.1 molar ratio in step S80 reacts with metal oxides such as B, W, and B-W in step S100, and the lithium:other metal molar ratio in the positive electrode active material does not decrease below 1:1, so no decrease in capacity occurs.
[0162] Regenerated cathode active material The recycled cathode active material of the present invention is characterized by being produced by the above-mentioned method for recycling a cathode active material. In this case, the ceramic is removed from the recycled cathode active material, which has the effect of significantly improving the rate performance of the battery.
[0163] In addition, the regenerated cathode active material of the present invention preferably includes one or more selected from the group consisting of lithium cobalt oxides such as LCO; lithium manganese oxides such as LiMnO2 or LiMn2O4; lithium iron phosphate compounds such as LiFePO4; lithium nickel cobalt aluminum oxide (NCA); lithium nickel oxides such as LiNiO2; nickel manganese-based lithium composite metal oxides in which part of nickel (Ni) in the lithium nickel oxide is replaced with manganese (Mn); and NCM-based lithium composite transition metal oxides in which part of nickel (Ni) in the lithium nickel oxide is replaced with manganese (Mn) and cobalt (Co), contains 1 to 10,000 ppm of Al2O3, and is characterized in that the surface is coated with a coating agent containing metal or carbon. In this case, there is an effect of being excellent in electrochemical performance, resistance characteristics, capacity characteristics, and the like.
[0164] More specifically, as an example, the regenerated cathode active material has the following Chemical Formula 1 [Chemical Formula 1] Li a Ni x Mn y Co z M w O 2+δ (In Chemical Formula 1 above, M includes one or more selected from the group consisting of B, W, Al, Ti, and Mg, 1 < a ≤ 1.1, 0 < x < 0.95, 0 < y < 0.8, 0 < z < 1.0, 0 ≤ w ≤ 0.1, −0.02 ≤ δ ≤ 0.02, and x + y + z + w = 1.) The compound represented thereby contains 1 to 10,000 ppm of Al2O3, and is characterized in that the surface is coated with a coating agent containing metal or carbon. In this case, there is an effect of being excellent in electrochemical performance, resistance characteristics, capacity characteristics, and the like.
[0165] The regenerated positive electrode active material preferably contains 1 to 4,000 ppm of Al2O3, more preferably 1 to 3,000 ppm, and within this range, there are advantages in that the long-term cycle characteristics and the balance of physical properties are excellent.
[0166] The regenerated positive electrode active material may preferably be a high nickel (High Ni) positive electrode active material having an Ni content of 65 mol % or more relative to the total amount of its metal elements.
[0167] The fluorine (F) content may be, for example, 5000 ppm or less, preferably 500 ppm or less, more preferably 100 ppm or less, and even more preferably 30 ppm or less. Within this range, excellent resistance and capacitance characteristics can be achieved.
[0168] The recycled cathode active material may be coated with a coating agent preferably containing metal or carbon. In this case, the structural stability of the cathode active material is improved without any chemical or physical changes to the cathode active material itself, thereby improving electrochemical properties such as output performance, life characteristics, and capacity. Furthermore, the surface of the cathode active material is substituted with a different element, reducing the amount of residual lithium and the pH, thereby improving physicochemical properties.
[0169] The regenerated cathode active material of the present invention can include all of the contents of the above-mentioned method for regenerating a cathode active material, and therefore, a redundant description thereof will be omitted here.
[0170] Preferred examples are presented below to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical idea of the present invention. Naturally, such changes and modifications also fall within the scope of the appended claims.
[0171] The waste stack cell used in the following examples was 28 cm x 10 cm (width x length), and was made by rolling together a positive electrode in which an NCM-based lithium transition metal composite oxide was coated on an aluminum foil; a separator coated with a PVdF-based binder and containing Al2O3; and a negative electrode made of graphite.
[0172] Comparative Example 1 <Positive electrode recovery process> The positive electrodes of the waste stack cells were manually stripped and collected (see Figure 3 below).
[0173] <Regeneration process of positive electrode active material> The recovered positive electrode was heat-treated in air at 550°C for 30 minutes to remove the binder and conductive material (see Figure 4 below). The temperature was increased at a rate of 5°C / min until the heat treatment temperature was reached.
[0174] Comparative Example 2 <Positive electrode recovery process> The waste stack cell was immediately placed in acetone or a mixed solvent of acetone and alcohol without being cut, and immersed for 60 minutes to allow swelling and impregnation, after which the positive electrode, negative electrode, and separator were separated (see Figure 5 below).
[0175] Comparative Example 3 <Positive electrode recovery process> The waste stack cell was cut in half and then immediately placed in acetone or a mixed solvent of acetone and alcohol without undergoing a compressed air injection process. After stirring for 60 minutes, the positive electrode, negative electrode, and separator were separated (see Figure 8c and d below).
[0176] Example 1 <Positive electrode recovery process> After cutting the side of the waste stack cell, compressed air was sprayed to separate the anode and some of the separator from the cathode, and only the cathode was collected (see Figure 6 below). The collected cathode was placed in acetone or a mixed solvent of acetone and alcohol and stirred for 10 minutes to collect a clean cathode with the separator and ceramic removed.
[0177] Example 2 <Positive electrode recovery process> In Example 1, the positive electrode was recovered in the same manner as in Example 1, except that the waste stack cell was cut into halves (see the photographs a and b in Figs. 7 and 8 below).
[0178] Example 3 <Positive electrode recovery process> As shown in Figure 9 below, the stack cell was cut into pieces approximately 3cm x 3cm in size, and then compressed air was sprayed onto the pieces to separate the positive electrode, negative electrode, and separator, and the positive electrode was recovered using the difference in specific gravity. After spraying compressed air for 10 minutes, more than 90% of the negative electrode was separated from the total of 300g of waste battery pieces, and the separator was also partially separated.
[0179] The recovered cathode pieces were placed in acetone or a mixed solvent of acetone and alcohol and stirred for 30 minutes. After stirring, the supernatant containing the separator was decanted and discarded, and the cathode pieces were collected and dried at 100°C for 10 hours.
[0180] Example 4 <Positive electrode recovery process> In Example 3, the positive electrode was recovered in the same manner as in Example 3, except that the stack cell was cut into pieces approximately 1 cm x 1 cm in size. For reference, because the size of the stack cell pieces was small, separation into the positive electrode, negative electrode, and separator was relatively incomplete compared to Example 3. This is presumably because the resistance of the stack cell pieces to the compressed air was small, preventing proper separation. However, this problem is believed to be surmountable by modifying the equipment or conditions.
[0181] Example 5 <Regeneration process of positive electrode active material> The dried positive electrode piece in Example 3 was cut into approximately 1 cm 2The resulting powder was then heat-treated in air at 550°C for 30 minutes to remove the binder and conductive material, and the positive electrode active material was separated from the current collector. The temperature was increased at a rate of 5°C / min to reach the heat treatment temperature.
[0182] To remove foreign materials such as LiF and metal fluorine present on the surface, 15 g of the recovered cathode active material was placed in 450 ml of a 0.1 wt % LiOH aqueous solution and stirred for 10 minutes. After the washing was completed, the cathode active material slurry was filtered to recover the washed cathode active material. The recovered cathode active material was dried at 100°C for 12 hours.
[0183] A lithium precursor, LiOH, was added to the dried cathode active material in an amount (0.09 mol) that would achieve the same molar ratio of lithium to other metals in the raw cathode active material (corresponding to the same molar ratio as in Comparative Example 1), and the resulting mixture was annealed in air at 750°C for 5 hours to prepare a recycled cathode active material. The molar ratio of lithium to other metals in the cathode active material was measured by ICP analysis.
[0184] For reference, the recycled cathode active material of Comparative Example 1 was obtained from the reference active material NCM651520, and its ICP analysis results showed that when the lithium to other metal ratio was 1.05, the lithium was reduced by approximately 0.1 mol ratio through the water washing process during recycling. However, due to measurement errors in ICP, the amount of added lithium in this example was set to 0.09-0.11 mol ratio. Other than that, there was no change in the composition of the other metals except for lithium.
[0185] After adding lithium and annealing at high temperature, a step of coating B or W for surface passivation may follow.
[0186] In the case of waste electrodes using high nickel (Ni 80 mol % or more) active material, after the lithium addition process (annealing process), a secondary water washing process (water: positive electrode active material = 0.5:1 to 2:1 weight ratio) to remove residual lithium may be included.
[0187] Examples 6 and 7 The positive electrode active materials were regenerated in the same manner as in Example 5, except that 0.10 mol and 0.11 mol of LiOH were used for annealing in the <regeneration step of positive electrode active material> of Example 5.
[0188] Comparative Example 4 The positive electrode active material was regenerated in the same manner as in Example 5, except that the stack cell pieces were not treated with acetone or a mixed solvent of acetone and alcohol in the <positive electrode recovery step> of Example 5, and 0.10 mol of LiOH was used during annealing in the <positive electrode active material regeneration step>.
[0189] Reference example Instead of recycled active materials, fresh NCM-based lithium composite transition metal oxide (NCM651520) was used.
[0190] [Test example] The properties of the positive electrodes and regenerated positive electrode active materials obtained in Examples 1 to 7, Comparative Examples 1 to 4, and Reference Example were measured by the following methods, and the results are shown in Table 1 below and FIGS.
[0191] *ICP analysis: Using an ICP analyzer, the remaining amount of LiF, the content of Al2O3, the ratio of lithium to other metals in the active material, and the content (mg / kg) of specific elements such as F were measured. This can be measured using a general ICP analyzer commonly used in laboratories, and there is no deviation due to the measurement device or method.
[0192] *Cell evaluation: 96 wt% recycled or virgin positive electrode active material, 2 wt% carbon black (conductive material), and 2 wt% PVdF (binder) were weighed and mixed with NMP to prepare a slurry. This was then coated onto aluminum foil to prepare a positive electrode. A coin half cell (CHC) was fabricated using the prepared positive electrode and 80 μL of a 3:7 (volume ratio) mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) as the electrolyte (EVPS). The electrochemical performance was evaluated under voltage cutoffs of 3 to 4.3 V and formation charge / discharge conditions of 0.1 C / 1.0 C (specific charge / discharge conditions: -0.1 C / 0.1 C, -0.33 C / 0.33 C, -0.5 C / 0.1 C, -0.5 C / 1 C, -0.5 C / 2 C).
[0193] [Table 1]
[0194] As shown in Table 1, the regenerated positive electrode active material according to the present invention (Examples 5 to 7) has superior charge / discharge capacity and efficiency compared to Comparative Example 4, which did not undergo the solvent treatment process according to the present invention, and was confirmed to be even closer to the newly produced positive electrode active material (Reference Example).
[0195] Figure 3 below shows photographs of the stack cell (a), the cathode (b) before stacking, and the front (c) and back (d) of the cathode manually separated from the stack cell in Comparative Example 1. It was confirmed that the ceramic coated on the separator was transferred to the entire cathode. Generally, separators are made of polymeric materials and are prone to shrinkage due to heat. To prevent this, the separator material is coated with ceramic on the order of tens to hundreds of nanometers. Since this ceramic is subjected to pressure during the lamination process when the separator and cathode are combined, the ceramic is transferred to the surface of the cathode when the cathode is physically separated.
[0196] Figure 4 below is a photograph of the cathode obtained in Comparative Example 1 after heat treatment to remove the binder and conductive material. It can be seen that the active material (black) and ceramic (white) that were detached from the current collector are mixed together. Even when sieved through a 325-mesh sieve, this mixture is impossible to separate because ceramic particles of several hundred nanometers are also present.
[0197] Figure 5 below shows photographs of a stack cell (a), a stack cell immersed in an acetone solution (b), a stack cell swelled and impregnated in the acetone solution (c), and the separated positive electrode, negative electrode, and separator (d) in Comparative Example 2. Here, it was confirmed that if the stack cell is immersed directly in the acetone solution without cutting, swelling takes a long time, making it difficult to directly separate the negative electrode in the acetone solution.
[0198] Figure 6 below shows photographs of (a) the side of a stack and folding cell, (b) the side of a cut stack and folding cell, (c) the stack and folding cell with an air jet sprayed onto the cut side, and (d) the positive electrode, negative electrode, and separator separated after the air jet spray in Example 1. Here, it was confirmed that although the stack cell can be separated into the negative electrode and the separator laminated on the negative electrode by spraying compressed air, it takes a long time due to the extra separator that is folded.
[0199] Figure 7 below shows photographs of a stack cell (a) cut in half and then separated using an air jet to separate the positive electrode, separator, and negative electrode in Example 2; a positive electrode (b) with a separator transferred from the separated stack cell; and a negative electrode and separator (c) recovered from the separated stack cell. It was confirmed that crushing the stack cell facilitated the separation of the negative electrode and the separator laminated on the negative electrode through the cut surface using compressed air. Separating the negative electrode first reduced the solvent treatment time and prevented the positive electrode, negative electrode, and separator from becoming entangled during the solvent treatment process. The positive electrode was then separated into a positive electrode or a combined positive electrode / separator electrode using an air jet.
[0200] Figure 8 below shows photographs of stack cells in Example 2 and Comparative Example 3, respectively, in the state (a, b) where they were treated with an acetone solution after air jet injection, and the state (c, d) where they were treated with an acetone solution without air jet injection. Here, in the case of stack cells in which the negative electrode was first separated by air jet, the separator was completely separated and floated in the supernatant after 10 minutes of immersion in the acetone solution. However, in the case of stack cells in which the negative electrode was not first separated by air jet, the separator was separated after 60 minutes of immersion in the acetone solution, but because the separator and negative electrode were precipitated between the positive electrode, they were not easily separated from each other.
[0201] Figure 9 below shows photographs of electrode pieces (c) obtained after cutting stack cells (a, b) into 3 cm x 3 cm pieces in Example 3, and the positive electrode (d), negative electrode, and separator (e) separated and recovered from the electrode pieces by treating them with an air jet. It was confirmed that, during the separation of 300 g of electrode pieces, more than 90% of the negative electrode was separated within the first 10 minutes, and some of the separator was also separated.
[0202] Figure 10 below is a photograph of the stack cell cut into 1 cm x 1 cm pieces and then treated with an air jet in Example 4. Here, it was confirmed that because the electrode pieces were small in size, many scattered when the air jet was sprayed, and they were unable to properly receive the air pressure, which actually reduced the separation performance.
[0203] FIG. 11 below shows the results of cell evaluation of the regenerated cathode active materials prepared in Examples 5 to 7 and Comparative Example 4, and the cathode active material of Reference Example (Reference NCM65). This graph shows the rate performance as a function of the number of cycles. This graph examines the rate performance by evaluating the capacity at different currents depending on the number of cycles. For reference, in the graph of FIG. 11, the horizontal axis represents the number of cycles, and the vertical axis represents the capacity. It was confirmed that when the cathode active material was regenerated without immersing the ceramic-transferred cathode in an acetone solution (Comparative Example 4), the charge / discharge capacity was inferior by 7 mAh / g or more compared to when the cathode active material was regenerated through the acetone solution immersion process (Examples 5 to 7) due to the higher ceramic content of the cathode active material. This is believed to be due to the increased resistance of the ceramic, which results in a decrease in charge / discharge capacity.
Claims
1. (a) crushing waste batteries including a positive electrode, a separator, and a negative electrode; (b) spraying compressed air onto the crushed waste batteries to remove the negative electrode; and (c) treating the waste batteries from which the negative electrode has been removed with a solvent to remove the separator and obtain positive electrode pieces, The method for regenerating a positive electrode active material, wherein the separator in step (a) is attached to the positive electrode by a ceramic coating.
2. The method for regenerating a positive electrode active material according to claim 1 , wherein the separation membrane in step (a) is a polymer separation membrane.
3. The method for regenerating a positive electrode active material according to claim 1 , wherein the waste battery in step (a) is a stack type cell.
4. The area of the crushed waste battery in step (a) is 1 cm 2 The method for regenerating a positive electrode active material according to claim 1 .
5. 2. The method for regenerating a positive electrode active material according to claim 1, wherein in the step (b), compressed air is injected into the waste battery to separate the negative electrode, and the separated negative electrode is discharged using centrifugal force.
6. The method for regenerating a positive electrode active material according to claim 1 , wherein the solvent in step (c) is a mixed solvent containing acetone and alcohol.
7. The method for regenerating a positive electrode active material according to claim 6 , wherein the alcohol is ethanol.
8. The method for regenerating a positive electrode active material according to claim 6, wherein the weight ratio of acetone to alcohol in the mixed solvent is 4:6 to 6:
4.
9. 2. The method of claim 1, further comprising the step of: (d) heat treating the obtained positive electrode pieces in air at 300 to 650° C. to recover the positive electrode active material.
10. The method for regenerating a positive electrode active material according to claim 9, further comprising the step of (e) washing the recovered positive electrode active material with water or a basic aqueous lithium compound solution having a content of more than 0% by weight and not more than 15% by weight.
11. The method for regenerating a positive electrode active material according to claim 10, wherein the washing in step (e) comprises mixing and stirring the recovered positive electrode active material with water or a basic aqueous lithium compound solution.
12. The method for regenerating a positive electrode active material according to claim 10, wherein in the step (e), the washed positive electrode active material is dried.
13. The method for regenerating a positive electrode active material according to claim 10, further comprising the step of (f) adding a lithium precursor to the washed positive electrode active material and annealing it in air at 400 to 1000°C.
14. The lithium precursor is LiOH, Li 2 CO 3 , LiNO 3 and Li 2 The method for regenerating a positive electrode active material according to claim 13, wherein the positive electrode active material is one or more selected from the group consisting of O.
15. (g) The method for regenerating a positive electrode active material according to claim 13, further comprising the step of coating the annealed positive electrode active material with a coating agent containing a metal or carbon, and then heat treating the same at 100 to 1200°C.
16. 2. The method for regenerating a positive electrode active material according to claim 1, wherein the positive electrode active material is at least one selected from the group consisting of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate compound, lithium nickel cobalt aluminum oxide, lithium nickel oxide, nickel manganese-based lithium composite metal oxide in which part of the nickel (Ni) in the lithium nickel oxide is replaced with manganese (Mn), and NCM-based lithium composite transition metal oxide in which part of the nickel (Ni) in the lithium nickel oxide is replaced with manganese (Mn) and cobalt (Co).
17. The regenerated positive electrode active material is Al 2 O 3 The method for regenerating a positive electrode active material according to claim 1, wherein the positive electrode active material contains 1 to 10,000 ppm of the above.
18. (a) crushing waste batteries including a positive electrode, a separator, and a negative electrode; (b) spraying compressed air onto the crushed waste batteries to remove the negative electrode; and (c) treating the waste batteries from which the negative electrode has been removed with a solvent to remove the separator and obtain positive electrode pieces, The method for recovering a positive electrode, wherein the separation membrane in step (a) is attached to the positive electrode by a ceramic coating.
Citation Information
Patent Citations
Method of recovering positive electrode active material from lithium battery, and reuse thereof
JP2010062105A
Treatment method for used lithium ion battery
JP2015195129A
How to recycle lithium-ion batteries
JP2019521485A
Precursor Synthetic method for lithium-ion secondary battery cathode active material from waste battery material, and manufacturing method of the cathode active material made by the same
KR1020170033787A
Pretreatment method for recycling lithium secondary battery
KR1020200077108A